Evaluation of prognostic factors in the surgical treatment of pulmonary metastases - Pawełczyk, Konrad; Marciniak, Marek; Błasiak, Piotr; Rzechonek, Adam (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : The resection of pulmonary metastases is a routine practice of thoracic surgery wards; however, clear protocols or prognostic factors defining the surgical treatment criteria are still not available. The aim of the study is to evaluate the prognostic factors associated with long-term survival in a group of patients who underwent resection of pulmonary metastases. Material and methods : A retrospective analysis was conducted on a group of 250 patients admitted to the Wrocław Thoracic Surgery Centre for radical resection of pulmonary lesions in the years 1996–2010. Results : The patients included in the study (n = 250) underwent 339 thoracotomies in total. The overall five-year survival was 52.8%. The univariate data analysis showed that the survival rate was significantly better in patients subjected to more than one thoracotomy (p = 0.01674). Among the other data, such as sex, tumour histology, disease-free interval (DFI) ≤ 12 and > 12 months, DFI ≤ 36 and > 36 months, age, number of tumours identified in CT and number of tumours subject to resection, operated side, resection type, radicality of resection, extent of lymphadenectomy, and adjuvant therapy, no statistical significance was observed in univariate and multivariate analysis (p > 0.05). Conclusions : Outcomes of re-metastasectomy are satisfactory if patients meet the baseline criteria for surgical treatment. None of the evaluated factors potentially influencing the patient survival was demonstrated to have any prognostic value. Further research, including the biology of tumours with pulmonary metastases, is necessary to select the group of patients that will benefit most from surgical treatment.